Fabrication of electrospun poly(lactic acid) nanoporous membrane loaded with niobium pentoxide nanoparticles as a potential scaffold for biomaterial applications. Issue 4 (16th October 2019) - Marins, Natália H.; Silva, Ricardo M.; Ferrua, Camila P.; Łukowiec, Dariusz; Barbosa, Ananda M.; Ribeiro, Juliana S.; Nedel, Fernanda; Zavareze, Elessandra R.; Tański, Tomasz; Carreño, Neftalí L. V.
Abstract: Tissue engineering aims to regenerate and restore damaged human organs and tissues using scaffolds that can mimic the native tissues. The requirement for modern and efficient biomaterials that are capable of accelerating the healing process has been considerably increased. In this work, a novel electrospun poly(lactic acid) (PLA) nanoporous membrane incorporated with niobium pentoxide nanoparticles (Nb2 O5 ) for biomaterial applications was developed. Nb2 O5 nanoparticles were obtained by microwave‐assisted hydrothermal synthesis, and different concentrations (0, 1, 3, and 5% wt/wt) were tested. Chemical, morphological, mechanical, and biological properties of membranes were evaluated. Cell viability results demonstrated that the membranes presented nontoxic effects. The incorporation of Nb2 O5 improved cell proliferation without impairing the wettability, porosity, and mechanical properties of membranes. Membranes containing Nb2 O5 nanoparticles presented biocompatible properties with suitable porosity, which facilitated cell attachment and proliferation while allowing diffusion of oxygen and nutrients. This study has demonstrated that Nb2 O5 nanoparticle‐loaded electrospun PLA nanoporous membranes are potential candidates for drug delivery and wound dressing applications.